High-Pitch Computed Tomography Coronary Angiography—A New Dose-Saving Algorithm: Estimation of Radiation Exposure - Dominik Ketelsen; Markus Buchgeister; Andreas Korn; Michael Fenchel; Bernhard Schmidt; Thomas G. Flohr; Christoph Thomas; Christoph Schabel; Ilias Tsiflikas; Roland Syha; Claus D. Claussen; Martin Heuschmid (Radiology Research and Practice)
Purpose. To estimate effective dose and organ equivalent doses of prospective ECG-triggered high-pitch CTCA. Materials and Methods. For dose measurements, an Alderson-Rando phantom equipped with thermoluminescent dosimeters was used. The effective dose was calculated according to ICRP 103. Exposure was performed on a second-generation dual-source scanner (SOMATOM Definition Flash, Siemens Medical Solutions, Germany). The following scan parameters were used: 320 mAs per rotation, 100 and 120 kV, pitch 3.4 for prospectively ECG-triggered high-pitch CTCA, scan range of 13.5 cm, collimation 64×2×0.6 mm with z-flying focal spot, gantry rotation time 280 ms, and simulated heart rate of 60 beats per minute. Results. Depending on the applied tube potential, the effective whole-body dose of the cardiac scan ranged from 1.1 mSv to 1.6 mSv and from 1.2 to 1.8 mSv for males and females, respectively. The radiosensitive breast tissue in the range of the primary beam caused an increased female-specific effective dose of 8.6%±0.3% compared to males. Decreasing the tube potential, a significant reduction of the effective dose of 35.8% and 36.0% can be achieved for males and females, respectively (𝑃<0.001). Conclusion. The radiologist and the CT technician should be aware of this new dose-saving strategy to keep the radiation exposure as low as reasonablly achievable.